(untitled) (Research, Society and Development, 2023)
The removal of fractured instruments during endodontic treatment is a challenge that can compromise the success of the procedure. The purpose of this case report is to highlight the efficacy and safety of using ultrasonic in conjunction with the orthodontic wire snare technique in removing fractured files, providing a reliable alternative for the treatment of these complicated situations. Patient, female, 57 years old, during an anamnesis, reported that an instrument had been fractured during a specialization course, without being able to specify the date of the occurrence. After radiographic evaluation, removal was indicated for correct obturation and subsequent placement of an intracanal pin. The procedure was performed in three sessions. In the first session, the crown was opened and the post was worn, which revealed the presence of a fractured file in the apical third of the root canal. In the second session, using ultrasonic and the appropriate uncertainties, grinding was performed around the fractured file. Then, a loop was made with orthodontic wire in a hypodermic needle, which resulted in the successful removal of the file. After confirming the removal of the instrument, the root canal was prepared and the endodontic treatment was completed in the third session. The case report highlights the effectiveness and safety of the combination of the loop technique with orthodontic wire and ultrasonic for the removal of fractured instruments in the root canal. This approach represents a reliable alternative for the treatment of complex situations during endodontics, ensuring the success of the procedure.